Controller with the Set Point Shift of Domestic Water Supply Control System - Gobis, V.; Baskys, A.; Zlosnikas, V.; Meile, E.; Platakis, A. (Elektronika ir Elektrotechnika, 2013)
The controller for domestic water supply feedback control system is developed and analyzed. It allows us to improve the control quality and save the energy consumed by the pump drive as compared to the case when PI controller is used. The simulation results of the control system are presented and discussed. The proposed controller is employed in the specialized frequency converter for domestic water supply systems. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5643